Perfil proteico e antigênico de isolados clínicos de Paracoccidioides SPP do estado de Mato Grosso - Queiroz Júnior, Luiz de Pádua (2013)
Works published by our research group has shown that clinical isolates have different serological reactivity patterns depending on the region of origin of the patient with Paracoccidioidomycosis (PCM).The results observed in reactions of Immunodiffusion (ID) against the commonly used exoantígenos containing glycoprotein of 43kDa predominating as (gp43) suggests that this fungus present regional variability. Authors already demonstrated by molecular biology techniques that exist a phylogenetic distance between isolates of Paracoccidoides spp according to the different regions of Latin America highlighted the Mato Grosso who performed with less genetic sharing index suggesting the existence of new species Paracoccidioides lutzii. In this work we aim to analyze the antigenic and immunogenic profile of 3 isolates of patients from State of the Mato Grosso and 2 isolates of patients from São Paulo, all affected by the PCM. Exoantigens were obtained using techniques already standardized from 5 selected clinical isolates being 2 of P. brasiliensis (Pb166 and Pb2880) and 3 from P. lutzii (PL2875, PL9840 and PL2912). The product of the obtaining of exoantigens was submitted to SDS-PAGE. The electrophoretic profile analysis demonstrated in SDSPAGE was carried out by comparing the bands with molecular weight used simultaneously with the selected exoantigens. The protein/glicoproteins profiles of the exoantigens of P. lutzii studied and obtained in the midst of Fava Netto were different from each other. The PL9840 isolate was which featured a larger number of distinct bands; the isolates PL2875 and PL2912 showed diffuse bands and a very intense band was observed in height between 50 and 60 kDa. The isolates of P. brasiliensis showed similarity in their protein profiles showing a band of low intensity (220 kDa) and a diffuse band situated between 50 and 60 kDa. The same was not observed with the isolates from P. lutzii who demonstrated different protein profiles when compared with each other and when compared with isolates of P. brasiliensis. The serum of the patient affected by PCM by P. lutzii (9840 serum) was only able to recognize their own exoantígenos (exo PL9840) not recognising other exoantígenos of P. lutzii. Note that isolated from P. lutzii demonstrate a significant antigenic variability. It is possible that this variability may explain differences who has occurred in serological reactivity patterns of patients affected by PCM ID tests when used exoantigens obtained from isolates from other regions front the exoantigens obtained from isolates from State of Mato Grosso. These results indicate new perspectives regarding protein, immunochemistry and the phylogenetics characterization of exoantigens of Paracoccidioides spp from Mato Grosso – Brazil.